A Case Study of Maternal Response to the Implied Antepartum Diagnosis of Inevitable Labor Dystocia. Issue 2 (16th January 2013) - McAlister, Barbara S.
ABSTRACT Two pregnant women, one obese and one of extremely small stature, received antepartum recommendations from their health care providers to schedule cesarean births. In response, both women sought providers who would support their desire to attempt vaginal birth. The women's perspectives on their birth experiences along with the pertinent medical record data from their pregnancies and births provide a reminder about the inherent normalcy of birth amid the current culture of interventive obstetrical practices.